PENGARUH PAPARAN MEDAN MAGNET EXTREMELY LOW FREQUENCY TERHADAP DERAJAT KEASAMAN (pH) UDANG VANAME - Qumairoh, Umayatul; Sudarti, Sudarti; Prihandono, Trapsilo (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2021)
ELF (Extremely Low Frequency) magnetic field is a spectrum of electromagnetic waves, where the frequency is less than 300 Hz and includes non-ionizing radiation. This study aims to examine the effect of exposure to ELF (Extremely Low Frequency) magnetic fields on the pH of vannamei shrimp. This research uses experimental research and uses a completely randomized design research. There are two groups in this study, namely the control group who are not exposed to magnetic fields and the experimental group who are exposed to magnetic fields. The experimental group was treated with exposure to an Extremely Low Frequency magnetic field with an intensity of 300 μT and 500 μT and an exposure time of 60 minutes, 90 minutes, and 120 minutes. The samples used were 145 shrimp samples of the same size. The experimental group had 120 samples and the control group had 25 samples. The data analysis technique used was SPSS 22 with the Kruskal-Wallis test. The result of the data analysis technique is exposure to ELF (Extremely Low Frequency) magnetic field affects the pH of vannamei shrimp.